A novel method for preparing phase-separated P2O5–Al2O3 glass with high Young's modulus. Issue 22 (15th November 2021) - Zhu, Qingong; Zhao, Gaoling; Cao, Zhiqiang; Jin, Junteng; Han, Gaorong
Abstract: In this paper, a new process for the phase-separated P2 O5 –Al2 O3 glass with SiO2 -rich region is presented. The new method combines pneumatic atomization with mechanical stirring based on melting-quenching preparation. X-ray diffraction, Nano-infrared spectra, X-ray photoelectron spectra, Raman scattering spectra and atomic force microscope were carried out to investigate sample's structure and surface morphology. The results show that the phase-separated glasses consist of second phase, transition region and matrix region. The average diameter of separated phase, ie. 500 nm, 150 nm, 76 nm and 85 nm, depends on the diameter of SiO2 glass particles prepared by ball milling, that is 50 μm, 10 μm, 2 μm and 400 nm respectively. Especially, transition region is formed by the connection of phosphorus oxygen tetrahedron and silicon oxygen tetrahedron, located between SiO2 region and matrix network region. After introducing the second phase, the Young's modulus of matrix glass was increased by 32.5% and the optimal value is 77.67 GPa within the scope of this experiment. It is attributed to that the formation of transition region increases the cross-linking of P2 O5 –Al2 O3 glass network. The Young's modulus of the phase-separated glass increases with the diameter of the quartz glass particles decreases from 50 μm to 2 μm, but weakens at a diameter of 400 nm. The network polymerization due to increasing in the number of P 3 units induced by second phase's diameter is responsible for rising in the Young's modulus, whereas too low diameter leads to particle agglomeration accompanied by the present of defects.